Hand-book for passengers over the Cambridge railroad : with a description of Mount Auburn cemetery / illustrated with engravings and a plan of the cemetery. (Tufts University. Tisch Library., 2015)
1 online resource (84, [1] pages, [2] leaves of plates) : illustrations, map, plan.; "Directory to avenues and paths"--Page 66-68.; "Business guide"--Page 72-84, [1] at end.; Printer statement from verso of title page.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.